Christian Hope as Seen by J. Ratzinger/Benedict XVI - Gardocki, Dariusz (Verbum Vitae, 2023)
One of the most pressing issues today is the need to rediscover hope, which can give meaning to life and history and enables people to walk together. After all, it is that spiritual force that does not allow a person to stop or be satisfied with what they already have and who they are. It provides an opening to the future and paves new paths for human freedom. It gives meaning to human life on earth. Christianity has an important role in this regard, as it is an event that was born out of hope and entered history as a living and profound experience of hope. In doing so, it touched some particularly tender place in the human being, which is precisely hope, without which the human being cannot live. The purpose of this article is to show the magnitude and meaningfulness of Christian hope based on the analysis of selected works of Joseph Ratzinger/Benedict XVI. To answer the question: what, according to him, is Christian hope, what is its basis and what is its specificity? What could it offer to the modern world? It is also an explanation of the thesis put forward by the author, which states that without God and without Christ there is no real hope, i.e. one that corresponds both to who man is and to the aspirations and desires arising from his ontic dignity. The first section addresses the reasoning behind hope from the perspective of anthropology. The second one presents and discusses the theological basis of Christian hope. Meanwhile, in the third section, the originality and specificity of Christian hope is shown.